Renal Impairment and Cardiovascular Disease in HIV-Positive Individuals: The D:A:D Study. (2nd August 2016) - Ryom, Lene; Lundgren, Jens D.; Ross, Mike; Kirk, Ole; Law, Matthew; Morlat, Philippe; Fontas, Eric; Smit, Colette; Fux, Christoph A.; Hatleberg, Camilla I.; de Wit, Stéphane; Sabin, Caroline A.; et al.
Abstract: Background. While the association between renal impairment and cardiovascular disease (CVD) is well established in the general population, the association remains poorly understood in human immunodeficiency virus (HIV)–positive individuals. Methods. Individuals with ≥2 estimated glomerular filtration rate (eGFR) measurements after 1 February 2004 were followed until CVD, death, last visit plus 6 months, or 1 February 2015. CVD was defined as the occurrence of centrally validated myocardial infarction, stroke, invasive cardiovascular procedures, or sudden cardiac death. Results. During a median follow-up duration of 8.0 years (interquartile range, 5.4–8.9 years) 1357 of 35 357 individuals developed CVD (incidence rate, 5.2 cases/1000 person-years [95% confidence interval CI, 5.0–5.5]). Confirmed baseline eGFR and CVD were closely related with 1.8% of individuals (95% CI, 1.6%–2.0%) with an eGFR > 90 mL/minute/1.73 m 2 estimated to develop CVD at 5 years, increasing to 21.1% (95% CI, 6.6%–35.6%) among those with an eGFR ≤ 30 mL/minute/1.73 m 2 . The strong univariate relationship between low current eGFR and CVD was primarily explained by increasing age in adjusted analyses, although all eGFRs ≤ 80 mL/minute/1.73 m 2 remained associated with 30%–40% increased CVD rates, and particularly high CVD rates among individuals with an eGFR ≤ 30 mL/minute/1.73 m 2 (incidence rate ratio, 3.08 [95% CI, 2.04–4.65]). Conclusions. Among HIV-positive individuals in a large contemporary cohort, a strong relation between confirmed impaired eGFR and CVD was observed. This finding highlights the need for renal preventive measures and intensified monitoring for emerging CVD, particularly in older individuals with continuously low eGFRs.